Rubéola, soroprevalência de anticorpos em puérperas e recém-nascidos durante a campanha de vacinação de 2008, em Botucatu, Brasil - Olbrich Neto, Jaime [UNESP]; Olbrich, Sandra Regina Leite Rosa [UNESP]; Mori, Natalia Leite Rosa; Rugolo, Ligia Maria Suppo de Souza [UNESP]; Kiy, Alice Maria (My University, 2011)
Objective: The present study evaluated the serological status of a representative and randomized sample of puerperae and their children to rubella during a vaccination campaign. Methods: This is a cross-sectional study of a representative and randomized sample of puerperae and newborns during a vaccination campaign that investigated their disease and vaccination histories. In children, the IgG titer against rubella was repeated at 9 months of age. Results: A total of 92 puerperae and 51 newborns were evaluated. The lowest positive status (66.6%), was found among women aged less than 20 years, and the highest (90.4%), among those aged 30 years or older. There was a strong correlation between mothers’ and newborns’ IgG. Among women with a history of exanthematous illness, mean IgG values were significantly higher. Most mothers (62.0%) did not know whether they had been vaccinated. At nine months, none of the children had detectable IgG levels. Conclusion: It is necessary to evaluate the seroprevalence of women in childbearing age since this group is very vulnerable.

Objetivo: Avaliar o estado sorológico contra rubéola de uma amostra, representativa e randomizada, de puérperas e seus filhos durante a campanha de vacinação. Métodos: Estudo transversal de amostra representativa e randomizada de puérperas e recém- -nascidos, durante campanha de vacinação, e inquérito sobre antecedente de doença e vacinas. Nas crianças, a dosagem de IgG contra rubéola foi repetida aos 9 meses de vida. Resultados: Noventa e duas puérperas e 51 recém-nascidos foram avaliados. A menor positividade (66,6%), foi encontrada entre as mulheres com menos de 20 anos, e a maior (90,4%), entre as com 30 ou mais anos de idade. Houve forte correlação entre IgG da mãe e do recém-nascido. Entre as mulheres com antecedentes de doença exantemática, os valores médios de IgG foram significativamente maiores. A maioria das mães (62,0%) não sabia informar se tinha recebido vacina anteriormente. Aos nove meses, nenhuma das crianças avaliada apresentou IgG detectável. Conclusão: É necessário avaliar a soroprevalência em mulheres em idade fértil e com menos de 20 anos, pois esse grupo acumula suscetíveis.
Rubella: seroprevalence of antibodies among puerperae and newborns during the 2008 vaccination campaign in Botucatu, Brazil
Keywords: Soroepidemiologic studies; Infant; Newborn; Rubella; Vaccines; Estudos soroepidemiológico; Recém-nascido; Rubéola; Vacinas